Rancangan Aplikasi Sistem Pengelolaan dan Pelaporan Aset di SMPN 218 dengan Metode Sequential Linear Waterfall menggunakan PHP dan MySQL Berbasis Web - Suparman, Yosep; Faizah, NM; Karo-Karo, Panser (Yayasan Kawanad, 2024)
Effective asset management is crucial for ensuring that assets are easily monitored and tracked. Currently, SMP Negeri 218 Jakarta manages assets manually by recording them in books before inputting them into spreadsheet software. This manual process results in suboptimal data management and asset reporting, leading to inefficiencies and increased risk of asset loss. The proposed solution is to design an asset management information system in the form of a web application to improve data handling and reporting efficiency. This study employs the PHP programming language within the Laravel framework and a MySQL database on the Xampp web server, utilizing the Sequential Linear (Waterfall) method. Functional testing of the system by web experts yielded a feature completeness score of 1, indicating its suitability and reliability for use in managing assets at SMP Negeri 218 Jakarta. The developed system aims to streamline asset management processes, enhance report accuracy, and provide timely access to asset data, ultimately supporting better decision-making and resource management within the school.